The Ratio of Abdominal Circumference and Body Weight – an Objective Parameter for the Daily Ward Round in a NICU? - Heimann, K.; Schoberer, M.; Posielek, J.; Fitzner, C.; Orlikowsky, T. (Klinische Pädiatrie, 2014)
Feeding tolerance and the degree of abdominal distension are important factors on the ward round on a NICU. They are basis for systematic changes in enteral feeds and an early indicator of clinical deterioration. Our aim was to examine the ratio of abdominal circumference (AC) to body weight (BW) as an additional variable for abdominal distension and its relationship to feeding, the increase of feeds and CPAP.The AC/BW ratio of premature infants decreases in serial measurements with increasing body weight during the first 28 days of life. Higher amount of enteral nutrition and CPAP cause an increase.In 30 premature infants (mean: 27.5 weeks, SD 2.2; 16 male, 2 200 measurements), daily measurement and recording during the first 28 days of life: AC (cm), BW (g), enteral/parenteral amount of fluid intake, type of formula, composition of macronutrients (breast milk, type of formula), gastric residual volume, CPAP therapy.Increase of AC ratio mean value from 19.9, SD 3.2 (d1) to 25.0, SD 5.2 (d6), followed by continuous decrease to 19.9, SD 4.4 (d28). Weeks of gestation, total amount of enteral feeding had a significant effect (p<0.05). With increasing total amount of enteral feeding, the AC/BW ratio decreased. Changes in enteral feeding volume, CPAP had no significant effect.Our aim was to provide longitudinal data from VLBW infants and to assess whether AC/BW ratio is affected by feeding, increase in feds and CPAP. In future the ratio may be a more objective parameter to avoid withholding feds or to detect early clinical deterioration.
Keywords: AC/BW ratio; abdominal circumference; body weight; enteral feeding; CPAP